Public Knowledge, Attitude and Stigma Towards Tuberculosis In Surabaya, Indonesia: Determining Associated Factors For Poor Attitude - Ilil Maidatuz Zulfa; Fitria Dewi Yunitasari (CV. Inara, 2025)
Tuberculosis (TB) is one of infectious disease that still remains a public health concern. Various factors affecting the TB treatment success rate including public knowledge, attitude, and stigma. Public knowledge and attitude directly associated with individual awareness that impacts TB transmission and early screenings for TB. This study aimed to assess public knowledge, attitude and stigma regarding TB in Surabaya, Indonesia and specifically analyzed the associated factors of having poor TB attitude. An observational, cross-sectional study was conducted using self-administered online questionnaire. Individuals age 18 years old or above were recruited at six different pharmacies in Surabaya during their visit and those who decided to withdraw after fulfilling the questionnaire were excluded. A total of 436 participants were recruited for this study. Of them, females were predominant (71.3%) and the majority of them were in the age groups of 18 to 30 years (69.3%). They were mostly had graduated from secondary school (60.3%). Concerning income, most of participants earned less than 1 million IDR. Regarding their levels of knowledge, attitude and stigma, the majority of them had good knowledge (50.7%), moderate attitude (47.5%), and positive stigma (93.1%). The significant associated factor of having poor attitude was knowledge which participants with good knowledge were less likely to have poor attitude (b= -1.103; OR = 0.332; p-value 0.000). Therefore, increasing level of public knowledge related to TB will significantly increase their attitude towards TB.